PENERAPAN ALGORITMA GENETIKA UNTUK MENYELESAIKAN PERMASALAHAN PENJADWALAN PERAWAT DENGAN FUZZY FITNESS FUNCTION (studi kasus : RS. BaliMed Denpasar) - , Desak Made Dwi Utami Putra ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Nurse scheduling is one of the problems that need more attentions to handle. This scheduling problem is complex with some constraints involved. There are two general constraints in the problem named, the hard constraints and the soft constraint. This research goal is to study the application of genetic algorithm for solving the nurse scheduling problem. However, this solving problem should satisfy all the hard constraints, and minimize the violation of the soft constraints. The good scheduling is not only satisfies the hard constraints defined, but also the preferences of each nurse. The genetic algorithm used in this research solved the nurse scheduling problem faced at BaliMed Hospital, Denpasar. The chromosome is the representation of the weekly scheduling of each nurse. This scheduling utilized fuzzy set to determine the fitness values of the chromosome. High member value represents high ideal level of solution. The result of this research is that the lower penalty value achieved from a solution, the more ideal scheduling got according to the membership degree in fuzzy set. Hopefully, this scheduling method can be an alternative solution for arranging a nurse scheduling.